The influence of phosphorus supplementation on the performance of beef weaners overwintering on kikuyu foggage and Smutsfinger hay - Van Niekerk, Willem A. (University of Pretoria, 2013)
Dissertation (MSc (Animal Science))--University of Pretoria, 2007.